AMS Standing Committee on New Skills 2010/2011: Report on the results of the expert groups - Wolfgang Bliem; Silvia Weiß; Gabriele Grün (Arbeitsmarktservice Österreich (AMS), 2012)
In October 2009 the Administrative Board of Public Employment Service Austria (AMS) set up an AMS Standing Committee on New Skills; this step - against the background of the difficult economic situation at that time - aimed at making use of periods when companies are characterised by weak capacity utilisation combined with labour market-policy support measures (such as educational leave, short-time work with qualification, AMS skills training measures) in order to prepare the labour force (i.e. employees in dependent employment and unemployed) on time for coming changes and challenges. But also independent of the respective economic situation there is urgent need to further develop the qualifications, knowledge and competences of the potential labour force with foresight to ensure that companies and the economic location of Austria overall remain competitive. In several workshops the AMS Standing Committee on New Skills aims to identify the companies' change processes by providing input from sectoral experts from major, innovative companies and institutions jointly with representatives of continuing education and training (CET) establishments and social partner organisations. These change processes allow conclusions to be drawn about current and future requirements for employees and job-seekers, which will in turn be integrated into the forwardlooking development of CET measures. It is the explicit objective of the AMS Standing Committee on New Skills to take timely qualification measures by anticipating these developments at an early stage and thus keep pace with the qualifications required in three to five years. In the period between November 2010 and June 2011, working groups were set up in the following four company clusters (in alphabetical order): Electrical engineering, electronics, telecommunications; Energy and environmental engineering; Healthcare and nursing; Wholesale and retail trade. The detailed results and statements of the four clusters were summarised in one short report each.
Keywords: 330